2006
DOI: 10.1007/s10856-006-9684-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing angiogenesis in collagen matrices by covalent incorporation of VEGF

Abstract: Since the survival of ingrowing cells in biomaterials for regenerative processes largely depends on the supply of nutrients and oxygen, angiogenesis plays an important role in the development of new materials for tissue engineering. In this study we investigated the possibility of enhancing the angiogenic properties of collagen matrices by covalent incorporation of the vascular endothelial growth factor (VEGF). In a previous paper we already reported the use of homo- and heterobifunctional cross-linking agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…These studies showed increased proliferation of ECs on VEGF-immobilized substrates. Koch and colleagues immobilized VEGF in 3D collagen matrices using a homobifunctional crosslinker, with the goal of enhancing angiogenesis in wound healing applications [41]. They demonstrated that ECs cultured in a 2D tissue culture plate showed increased proliferation upon exposure to VEGF-immobilized collagen matrices in vitro; furthermore, VEGF-immobilized collagen matrices enhanced angiogenesis of the surrounding environment upon implantation into the chorioallantoic membrane of the chicken embryo.…”
Section: Resultsmentioning
confidence: 99%
“…These studies showed increased proliferation of ECs on VEGF-immobilized substrates. Koch and colleagues immobilized VEGF in 3D collagen matrices using a homobifunctional crosslinker, with the goal of enhancing angiogenesis in wound healing applications [41]. They demonstrated that ECs cultured in a 2D tissue culture plate showed increased proliferation upon exposure to VEGF-immobilized collagen matrices in vitro; furthermore, VEGF-immobilized collagen matrices enhanced angiogenesis of the surrounding environment upon implantation into the chorioallantoic membrane of the chicken embryo.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, a potent angiogenic factor, VEGF, was covalently incorporated into collagen gels using homobifunctional crosslinking reagent directed to thiol groups in collagen and VEGF. When implanted on chicken chorioallantoic membrane, the collagen gels modified with VEGF enhanced capillary formation and tissue ingrowth [47]. VEGF also has been genetically modified to express N-terminal cysteine, and the recombinant protein was conjugated to fibronectin via thiol-directed bifunctional crosslinking reagent without loss in bioactivity [48].…”
Section: Modifications With Signalingmentioning
confidence: 99%
“…11,16 Synthetic collagen model systems, also known as collagen mimetic peptides (CMPs), have been useful in elucidating collagen structure and factors responsible for the stabilization of the triple helix. 9,[17][18][19] CMPs form a triple helical structure almost identical to that of natural collagens; however, unlike collagen molecules, CMPs are small (<3 KDa) and, therefore, exhibit reversible melting behaviors. 11,13,17 CMPs based on ProProGly or ProHypGly trimers have been widely studied and their melting temperatures (T m ) vary from 21 to 75 °C, depending on the molecular weight and amino acid composition.…”
Section: Introductionmentioning
confidence: 99%